Nectar Replaced by Volatile Secretion: A Potential New Role for Nectarless Flowers in a Bee-Pollinated Plant Species - Guimarães, Elza; Tunes, Priscila; Almeida Junior, Luiz D. de; Di Stasi, Luiz C.; Dötterl, Stefan; Machado, Silvia R. (Frontiers in Plant Science, 2018)
The presence of nectarless flowers in nectariferous plants is a widespread phenomenon in angiosperms. However, the frequency and distribution of nectarless flowers in natural populations, and the transition from nectariferous to nectarless flowers are poorly known. Variation in nectar production may affect mutualism stability, since energetic resource availability influences pollinators’ foraging behaviour. Here we described the spatial and temporal nectar production patterns of Jacaranda oxyphylla, a bee-pollinated species that naturally presents nectarless flowers. Additionally, we compared nectariferous and nectarless floral disks in order to identify histological, subcellular and chemical changes that accompanied the loss of nectar production ability. For that we used standard methods for light and transmission electron microscopy, and gas chromatography coupled to mass spectrometry for chemical analyses. We verified that 47% of flowers did not produce nectar during the whole flower lifespan (nectarless flowers). We also observed remarkable inter-plant variation, with individuals having only nectarless flowers, others only nectariferous ones and most of them showing different proportions of both flower types, with variable nectar volumes (3-21 µl). Additionally, among nectariferous flowers, we registered two distinct rhythms of nectar production. ‘Early’ flowers produced nectar from 0 to 24 hours, and ‘late’ flowers produced nectar from 24 to 48 hours of anthesis. Although disks from nectariferous and nectarless flowers displayed similar histological organization, they differed strongly at subcellular level. Nectariferous (‘early’ and ‘late’) flowers exhibited a cellular apparatus typical of nectar secretion, while nectarless flowers exhibited osmophoric features. We found three aliphatic and one aromatic compound(s) that were detected in both the headspace of flowers and the disks of nectarless flowers, but not the disks of nectariferous flowers Although the remarkable variation in nectar availability may discourage pollinator visits, nectarless flowers might compensate it by producing volatile compounds that can be part of floral scent, acting as chemical attractants. Thus, nectarless flowers may be helping to maintain pollination in this scenario of trophic resource supply scarcity. We suggest that J. oxyphylla can be transitioning from a nectar-based pollination system to another resource-based or even to a deceit mechanism of pollination.